2020
DOI: 10.1183/16000617.0057-2019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pharmacological interventions on quality of life and fatigue in sarcoidosis: a systematic review

Abstract: AimsMany sarcoidosis patients experience a reduction in health-related quality of life (HRQoL) and a majority of patients report fatigue. Historically, drug trials in sarcoidosis have focused on changes in chest radiographs, lung function parameters and biomarkers, while HRQoL and fatigue have not been the main outcomes examined. We performed a systematic review of the literature to evaluate the existing evidence on the effects of pharmacological interventions on HRQoL and fatigue outcomes.MethodsThe systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Medical therapeutic options for such systemic conditions are often limited, reflecting the complex nature and heterogeneous pathophysiologic origins [33]. Limited data in the medical literature have shown a beneficial effect of PR intervention among individuals with sarcoidosis resulting in an improvement of fatigue and dyspnea symptoms as well as improved exercise capacity and quality of life.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Medical therapeutic options for such systemic conditions are often limited, reflecting the complex nature and heterogeneous pathophysiologic origins [33]. Limited data in the medical literature have shown a beneficial effect of PR intervention among individuals with sarcoidosis resulting in an improvement of fatigue and dyspnea symptoms as well as improved exercise capacity and quality of life.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…GCs may offer benefits in newly diagnosed, symptomatic, untreated patients, but in those already treated and clinically stabilized, an increase in daily dose of GCs and/or addition of other drugs may often not be useful. Some small trials with stimulants have found them well tolerated and effective [85].…”
Section: Management Of Eye Neurological and Cardiac Sarcoidosismentioning
confidence: 99%
“…However, fatigue is common in all chronic disorders, for instance, chronic obstructive pulmonary disease, liver disease, rheumatic diseases, sarcoidosis, cancer, hematologic diseases, and many others. 1,[8][9][10][11][12][13] Thus, while many published papers assess fatigue as a unique feature of a specific disease (eg, the literature contains many references to cancer-related fatigue [CRF]), we believe central fatigue is a feature common to many if not all chronic diseases.…”
mentioning
confidence: 99%
“…6,13,14 Thus, one must conclude that fatigue can be improved by treatment of the underlying condition only to a minor degree. 10,14 There are studies that exercise may improve fatigue in most chronic disorders, but prospective, randomized studies are necessary to confirm this in CIDP. 8,11,12 Many other items that are related to and impact fatigue but are not specific to the disease in question are known, including age, gender, obstructive sleep apnea, poor sleep, depression, anxiety, personality type, and life experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation